Simulation of the pulsating current traction motor - Yuriy M. Kulinich; Sergey A. Shukharev; Denis Yu. Drogolov (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
Design and improvement of traction electric engines ensuring reduction of the railway transportation power consumption is a current long-term objective. The objective is to develop technical requirements to the new electric engines, including implementation of the set haulage performance of locomotive, providing for constant power in the certain range of the running speed, as well as required properties in case of the supply network parameters change, selection of the weight and dimensions parameters ensuring fitting of the traction electric engines in the locomotive underframe, and other important tasks. The new technology is proposed for forecasting the engine properties using simulation modeling of the hauling features and electrical characteristics of engine in order to resolve the above mentioned objectives. The proposed pulsating current traction motor model takes into account the eddy currents effect on the processes of magnetic flux changes in the engine steel and the nature of electromagnetic processes in the engine. Electric component of the engine simulation model is added with the torque mechanical balance equation that allows assessing its operating properties to the full extent. Results of calculations are presented in the form of the engine electromotive force attenuation curve calculated for specific mode of operation at the armature current of 780 A and the initial value of electromotive force amounting to 525 V. Obtained parameter of attenuation correlates with the experimental data presented in the other information source. Value of determination factor between the specified curves certifies adequacy of the developed simulation model. Proposed model of engine and methodology of its design allows modeling its operation in transition and in static modes of operation. Engine properties obtained by means of the proposed simulation model n = f(iа) and M = f(iа) are almost similar to the properties of traction engine NB-514 in the entire range of the armature current change iа. Proposed simulation model allows designing pulsating current traction motor with the set operating properties, as well as studying the engine parameters effect on its energy indicators.